2017
DOI: 10.24071/jpsc.142569
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Analysis Between the Service Quality, Customer Satisfaction, and Customer Loyalty of Viva Generik Pharmacy in Semarang

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…Trained pharmacists and assistant pharmacists play an important role in recommending over-the-counter drugs to first-time buyers (Emmerton and Shaw, 2002). Service quality affects customer satisfaction and customer loyalty (Monica, Dharmmesta and Syahlani, 2017). Satisfied patients are more likely to continue to use health care services, value and maintain relationships with health care providers, adhere to treatment, and have better health outcomes (Naik Panvelkar, Saini and Armour, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Trained pharmacists and assistant pharmacists play an important role in recommending over-the-counter drugs to first-time buyers (Emmerton and Shaw, 2002). Service quality affects customer satisfaction and customer loyalty (Monica, Dharmmesta and Syahlani, 2017). Satisfied patients are more likely to continue to use health care services, value and maintain relationships with health care providers, adhere to treatment, and have better health outcomes (Naik Panvelkar, Saini and Armour, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Service Quality yang makin baik pada sektor UMKM dapat berpengaruh terhadap peningkatan loyalitas konsumen (Eva et al, 2017). Namun berbeda yang ditemukan oleh Candra, (2020) bahwa Service Quality tidak berpengaruh terhadap loyalitas konsumen.…”
Section: Pendahuluanunclassified
“…These results showed that service quality influenced customer satisfaction. The company must increase customer perception for increasing customer satisfaction (Monica et al, 2017). E-service quality had a significant effect on perceived value.…”
Section: Introductionmentioning
confidence: 99%